Groovy the colors of Pacita Abad - Sogueco, Milo 1976-.; Yaneza, Hilda; Amar, Layla Tanjutco; Cultural Center of the Philippines; Studio M Production; CCI Living Asia.; Fundacion Pacita ([Manila] CCP, 2005)
A documentary on the life and work of Filipino artist, Pacita Abad; her childhood years in Batanes Island, Philippines; interviews with Pacita's family; Pacita's life as a student in the University of Philippines; interview with husband, Jack Garrity on how Pacita started her painting career and their travels around the world; Pacita's inspiration on her art from India; interviews with Pacita's friends; Pacita's development as an artist; her "trapunto" technique of painting; the social consciousness which influenced her art; learning how to swim and scuba dive; her fascination with masks and Indonesian wayang puppetry; the various ethnic influences on her paintings; her courage in facing her illness; her residency at the Singapore Tyler Print Institute; painting the first art bridge in Singapore; art exhibition in Philippines; homecoming to Batanes Island.
Summary from http://misas.nhb.gov.sg.
Executive producers, Cultural Center of the Philippines, Milo Sogueco ; produced by Milo Sogueco, Hilda Yaneza ; screenplay by Layla Tanjutco-Amar ; Directors of photography, Arnold Tañare, Milo Sogueco ; music by Earl Francis de Veyra ; editor, Carolyn Eguaras ; voice-over by Ma. Hilda Yaneza.
Keywords: Abad, Pacita -- 1946-2004.; Women artists -- Philippines -- Biography; Paintings -- Philippines